Real-world experience of first-line afatinib in patients with EGFR-mutant advanced NSCLC: a multicenter observational study - Ho, Gwo Fuang; Chai, Chee Shee; Alip, Adlinda; A. Wahid, Mohd Ibrahim; Abdullah, Matin Mellor; Foo, Yoke Ching; How, Soon Hin; Zaatar, Adel; Lam, Kai Seng; Leong, Kin Wah; Low, John Seng Hooi; Md Yusof, Mastura; et al. (BioMed Central Ltd., 2019)
Abstract Background: This study aimed to evaluate the efficacy, side effects and resistance mechanisms of first-line afatinib in a real-world setting. Methods: This is a multicenter observational study of first-line afatinib in Malaysian patients with epidermal growth factor receptor (EGFR)-mutant advanced non-small cell lung cancer (NSCLC). Patients’ demographic, clinical and treatment data, as well as resistance mechanisms to afatinib were retrospectively captured. The statistical methods included Chi-squared test and independent t-test for variables, Kaplan-Meier curve and log-rank test for survival, and Cox regression model for multivariate analysis. Results: Eighty-five patients on first-line afatinib from 1st October 2014 to 30th April 2018 were eligible for the study. EGFR mutations detected in tumors included exon 19 deletion in 80.0%, exon 21 L858R point mutation in 12.9%, and rare or complex EGFR mutations in 7.1% of patients. Among these patients, 18.8% had Eastern Cooperative Oncology Group performance status of 2–4, 29.4% had symptomatic brain metastases and 17.6% had abnormal organ function. Afatinib 40 mg or 30 mg once daily were the most common starting and maintenance doses. Only one-tenth of patients experienced severe side-effects with none having grade 4 toxicities. The objective response rate was 76.5% while the disease control rate was 95.3%. At the time of analysis, 56 (65.9%) patients had progression of disease (PD) with a median progression-free survival (mPFS) of 14.2 months (95% CI, 11.85–16.55 months). Only 12.5% of the progressed patients developed new symptomatic brain metastases. The overall survival (OS) data was not mature. Thirty-three (38.8%) patients had died with a median OS of 28.9 months (95% CI, 19.82–37.99 months). The median follow-up period for the survivors was 20.0 months (95% CI, 17.49–22.51 months). Of patients with PD while on afatinib, 55.3% were investigated for resistance mechanisms with exon 20 T790 M mutation detected in 42.0% of them. Conclusions: Afatinib is an effective first-line treatment for patients with EGFR-mutant advanced NSCLC with a good response rate and long survival, even in patients with unfavorable clinical characteristics. The side-effects of afatinib were manageable and T790 M mutation was the most common resistance mechanism causing treatment failure.